2002
DOI: 10.1096/fj.02-0287fje
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of AP‐1 in human bladder epithelial cells by inorganic and methylated arsenicals

Abstract: Chronic exposures to inorganic arsenic (iAs) have been linked to increased incidences of various cancers, including cancer of the urinary bladder. Mechanisms by which iAs promotes cancer may include stimulation of activator protein-1 (AP-1) DNA binding through increased expression and/or phosphorylation of the AP-1 constituents. However, the role of methylated metabolites of iAs in AP-1 activation has not been thoroughly examined. In this study, we show that short-time exposures to 0.1-5 microM arsenite (iAsII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…We have also shown that UROtsa cells do not express AS3MT . Importantly, comparison of our previous work (Drobná et al, 2003;Lin et al, 2002;) with results of the present study suggests that serum starvation for 16 h has no effect on AS3MT expression or on the metabolic pattern of iAs in UROtsa cells.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…We have also shown that UROtsa cells do not express AS3MT . Importantly, comparison of our previous work (Drobná et al, 2003;Lin et al, 2002;) with results of the present study suggests that serum starvation for 16 h has no effect on AS3MT expression or on the metabolic pattern of iAs in UROtsa cells.…”
Section: Discussionsupporting
confidence: 74%
“…However, no details regarding the speciation technique or data validation are provided. Our studies on the metabolism and toxic effects of As in UROtsa cells (Drobná et al, 2003;Styblo et al, 2000Styblo et al, , 2002 have consistently shown that these cells do not methylate iAs. Notably, T24 cells, another cell line derived from human bladder epithelium, also lack the capacity to methylate iAs (Styblo et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations